Sistem Pidana dan Tindakan â€œDouble Track Systemâ€ Dalam Hukum Pidana di Indonesia - Barda Nawawi Arief, Purwoto, Gita Santika Ramadhani, (Diponegoro Law Journal, 2012)
In the field of law, it is necessary to have balance between statutory rules, law enforcement, and society. Law which is identical with sanction issue, now, is still used as an effort to prevent crime. Yet, in the development of modern law, there is segregation between criminal sanction and treatment that is commonly known as double track system. In Indonesia, there is a lack in the criminal sanction system and treatment in the criminal case. The lack is that an inconsistent or overlapping between criminal sanction and treatment specifically additional criminal with treatment. The system of criminal sanction with treatment is regulated more systematic in the concept of KUHP by concerning on interest and balance between the effort to achieve social welfare and social defence. Therefore, there should be a clear formulation between criminal sanction and treatment. Moreover, in the decision to put sanction, it is necessary to concern on the purpose of punishment, and the treatment does not include as supplement in a statutory rules.